2020
DOI: 10.3390/ijms21186826
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of DYRK1A Identified by Computational and Experimental Approaches

Abstract: Dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) is a protein kinase with diverse functions in cell regulation. Abnormal expression and activity of DYRK1A contribute to numerous human malignancies, Down syndrome, and Alzheimer’s disease. Notably, DYRK1A has been proposed as a potential therapeutic target for the treatment of diabetes because of its key role in pancreatic β-cell proliferation. Consequently, DYRK1A is an attractive drug target for a variety of diseases. Here, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“… 30 , 31 As a result of these findings, selective Dyrk1A inhibitors have emerged as an attractive drug target for a variety of diseases. 32 However, whether Dyrk1A is involved in the pathogenesis of depression, in particularly its potential role during cell death and signalling pathways, is not clearly understood. In the present study, with use of a bilaterally intracerebral injection of AAV‐miR‐211‐5p virus into the CA1 area of CUMS rats to overexpress miR‐211‐5p, we found that a significant reduction in Dyrk1A expression levels was observed, effects which paralleled the decreases in pro‐apoptotic proteins BAX, Caspase‐3 and Caspase‐9 levels along with an up‐regulation in the levels of the anti‐apoptotic protein, Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 As a result of these findings, selective Dyrk1A inhibitors have emerged as an attractive drug target for a variety of diseases. 32 However, whether Dyrk1A is involved in the pathogenesis of depression, in particularly its potential role during cell death and signalling pathways, is not clearly understood. In the present study, with use of a bilaterally intracerebral injection of AAV‐miR‐211‐5p virus into the CA1 area of CUMS rats to overexpress miR‐211‐5p, we found that a significant reduction in Dyrk1A expression levels was observed, effects which paralleled the decreases in pro‐apoptotic proteins BAX, Caspase‐3 and Caspase‐9 levels along with an up‐regulation in the levels of the anti‐apoptotic protein, Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 , 12 , 19 , 35 ]. The level of activity of DYRK1A is of key importance for its physiological and pathological effects [ 24 , 36 , 37 ]. Hence, DYRK1A is regulated based on both gene expression and protein abundance (for reviews see [ 34 , 35 , 36 , 38 ]) with both low and high expression exerting significant effects on human diseases ( Table 1 ).…”
Section: Dyrk1a Expression and Enzymatic Activitymentioning
confidence: 99%
“…For the last 20 years, many studies have demonstrated that DYRK1A dosage and activity play a key role across a variety of human diseases ( Figure 3 ) [ 37 , 114 , 130 , 131 , 132 , 133 , 134 , 135 ]. Over the past decade, the development of novel treatments to regulate DYRK1A activity in cell models and mouse models has exploded.…”
Section: Dyrk1a a Target For The Patient’s Futurementioning
confidence: 99%
“…Finally, a number of other selective inhibitors have been reported though structure-based discovery ( 119 123 ). From these advanced studies, it appears that we are close to identifying clinically viable compounds for multiple indications, including metabolic, neurologic, and oncologic disorders.…”
Section: Introductionmentioning
confidence: 99%